IMPLEMENTASI PERMAINAN BUAH ROMAWI UNTUK MENINGKATKAN HASIL BELAJAR BILANGAN ROMAWI PADA SISWA KELAS IV SD - Sriyati Sriyati (Khazanah Pendidikan, 2021)
This study aims to improve learning outcomes of Roman numerals through the Buah Romawi game in grade IVa students at SD Negeri Pacitan. The type of research used is Classroom Action Research. As the research subjects were 32 students of grade IVa at SD Negeri Pacitan. As the research object is the learning outcomes of Roman numerals obtained from learning. Data collection techniques using observations, tests and documentations. The data analysis technique used is descriptive analysis. The results showed that learning through the Buah Romawi game could improve the learning outcomes of grade IVa students at SDN Pacitan. The average score of student’s learning outcomes obtained from the pre-cycle test was 58.75, increasing to 64.53 in the first cycle and increasing again to 71.72 in the second cycle. The percentage of classical class completeness at the pre-cycle stage was 25% (8 students completed), increased to 41% (13 students completed) in first cycle and increased again to 75% (24 students completed) in second cycle. With the success indicators of Classroom Action Research that have been achieved, it can be concluded that the implementation of the Buah Romawi game can improve the learning outcomes of Roman numerals in grade IVa students at SD Negeri Pacitan.